Blinded by the light [compact disc] : original motion picture soundtrack. - Rahman, A. R; Springsteen, Bruce (Legacy Recordings, 2019)
The music of Bruce Springsteen plays a vital role in the latest film from Gurinder Chadha, the director of Bend It Like Beckham. Along with new and previously unreleased Springsteen music, there is new music from Academy Award winner A.R. Rahman.